Platinum-group elements (PGE) in the New Afton alkalic Cu-Au porphyry deposit, Canadian Cordillera, II: PGE distribution and models for the hydrothermal coprecipitation of Co-Ni-Pd-Pt in pyrite - Robb, Samuel J.; Boucher, Brandon M.; Mungall, James E.; Hanley, Jacob J. (Frontiers in Earth Science, 2023)
Occurrences of significant concentrations of platinum-group elements (PGE) in porphyry deposits have seen limited attention and the geochemical controls on their deposition have been poorly understood. New Afton is a late Triassic alkalic Cu-Au porphyry deposit situated 10 km west of Kamloops, British Columbia with Pt and Pd enrichments locally exceeding 30 ppm. Primary PGE deposition accompanied hypogene Cu-Au mineralization linked to potassic alteration, with Pt and Pd deportment dominated by their inclusion in early Ni- and Co-rich pyrite with subsidiary amounts of platinum-group minerals (PGM) mertieite-II, isomertieite > temagamite, kotulskite. Secondary alteration of hypogene PGE-rich pyrite promoted remobilization of PGE, creating vein-controlled PGE enrichment where essentially all Pt and Pd are hosted by PGM dominated by temagamite > mertieite-II, and sperrylite, leaving behind complementary PGE-depleted domains. Thermodynamic modelling shows that primary co-precipitation of Pt with Co and Pd with Ni can be explained solely through the cooling of a hydrothermal system, regardless of whether the mineralizing fluid was a brine or a low-density vapour. Pd and Pt were transported from an underlying magma reservoir into the porphyry system by a magmatic-hydrothermal fluid as Cl- complexes. Pt-rich cobaltian pyrite formed at high temperatures, whereas Pd-rich nickeliferous pyrite formed at somewhat lower temperatures. Zonation of metals in pyrite suggests that PGE were incorporated in pyrite under conditions of fluctuating fluid temperatures during transport and cooling of orthomagmatic fluids at the main Cu-Au mineralization stage. There exists a hitherto overlooked potential for significant Pt and Pd mineralization in early hypogene pyrite that may be spatially separated from visible Cu mineralization, especially in potassic or ultrapotassic systems.